Cancer in the Arab World 2022
DOI: 10.1007/978-981-16-7945-2_23
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in the Arab World

Abstract: The recent rapid modernization of life in the Arab region has led to major changes in the lifestyle and attitude of Arab people. This has subsequently resulted in an obvious change in the disease burden profile where the Non-Communicable Diseases (NCDs) exert a huge burden in the region. The main factors that have been attributed to this increase in NCDs are the increased incidence of obesity, physical inactivity, stressful busy life, smoking, and dietary habits. Cancer is among the top NCDs that has increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Especially for CRC, population screening is particularly low because it is not accepted by local communities due to religious and cultural barriers and a high rate of mistrust regarding the effectiveness of screening. This as mentioned above interprets the advanced stage of CRC at diagnosis which implies an unfavorable outcome[ 58 ]. Some countries, such as Qatar, have begun to implement national healthcare transformation programs with proposals that might be adopted by other Middle Eastern countries.…”
Section: Etiopathogenetic Factorsmentioning
confidence: 99%
“…Especially for CRC, population screening is particularly low because it is not accepted by local communities due to religious and cultural barriers and a high rate of mistrust regarding the effectiveness of screening. This as mentioned above interprets the advanced stage of CRC at diagnosis which implies an unfavorable outcome[ 58 ]. Some countries, such as Qatar, have begun to implement national healthcare transformation programs with proposals that might be adopted by other Middle Eastern countries.…”
Section: Etiopathogenetic Factorsmentioning
confidence: 99%
“…The first author (SJM), a qualitative female researcher (PharmD), conducted in-person interviews at JUH, a large semigovernment tertiary hospital in Amman, Jordan. The semistructured interview guide was based on an a priori framework and a literature review of CRC survivors' experiences, with an emphasis on cancer-related literacy (1)(2)(3)(30)(31)(32)(33)). An open-ended biographical framework and probing questions were used to better capture patients' complex interactions with healthcare services throughout their journey.…”
Section: Participants and Recruitment Crc Survivors' Interviewsmentioning
confidence: 99%
“…In Asia, Eastern Europe, and South America, CRC incidence and death have risen rapidly. The Arab population is not an exception; although having lower rates of CRC than western nations, the illness has been growing in Arab nations over the last decade ( 2 ). CRC is Jordan's second most frequent occurring malignancy and the most common among men.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, the age-standardised rate per 100,000, was 8.4 [ 1 ], which is generally lower than that in other parts of the world, with notable heterogeneity from regional and country-level perspectives [ 2 ]. Data from the Middle East and North Africa show a comparatively rising trend [ 3 ]. CRC has emerged as a growing health concern in Algeria owing to the severity of the disease, as its incidence rate continues to rise.…”
Section: Introductionmentioning
confidence: 99%
“…CRC is a complex and multifactorial neoplasm that is influenced by a variety of factors, including genetics, environment and lifestyle [ 5 8 ]. Previous studies have shown that the incidence, prevalence and clinical characteristics of CRC vary depending on geographic and demographic factors [ 3 , 9 11 ].…”
Section: Introductionmentioning
confidence: 99%